Arka Nikita – New GMS based okra F1 hybrid - Pitchaimuthu, M; Dutta, O P; Rao, E Sreenivasa; Hebbar, S Shankar; K, Divya S; T, Chaithra L (Indian Horticulture, 2021)
Arka Nikita is F1 okra hybrid with dark green, smooth, five ridged fruits; high yield (21.0-24.0 t/ha) and tolerant to YVMV and suitable for both kharif and rabi seasons. It is well adapted to okra growing regions of Karnataka, Andhra Pradesh, Bihar, Orissa, West Bengal, Tamil Nadu, Haryana, Maharashtra and Andaman and Nicobar Islands. Arka Nikita is F1 hybrid cross between GMS-4 × IIHR -299-1., and is being evaluated at 11 centres of All India Co-ordinated Vegetable Improvement Project AICRP(VC) and five centres each of UHS, Bagalkot, Zonal Advisory Research Council Southern Zone , Southern Transition zone (Zone- 7) and Central Dry Zone–IV of Karnataka. So far around 750 kgs of hybrid seeds were sold and it has covered more than 300 acres of okra growing states in the country. It is a first commercial genetic male sterile based F1 hybrid from the public Institutions in the country and the world. It is very much suitable for precision farming (Drip irrigation, mulching and fertigation system). It has also come up very well for organic cultivation with palak as intercrop.